2021
DOI: 10.3390/jcm10245799
|View full text |Cite
|
Sign up to set email alerts
|

Long COVID a New Derivative in the Chaos of SARS-CoV-2 Infection: The Emergent Pandemic?

Abstract: Coronavirus disease 2019 (COVID-19) is a multisystem illness caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), which can manifest with a multitude of symptoms in the setting of end-organ damage, though it is predominantly respiratory. However, various symptoms may remain after acute SARS-CoV-2 infection, and this condition is referred to as “Long COVID” (LC). Patients with LC may develop multi-organ symptom complex that remains 4–12 weeks after the acute phase of illness, with symptoms in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 80 publications
(144 reference statements)
0
39
0
3
Order By: Relevance
“…Long-COVID-19 emerges as a new aspect of the public health crisis triggered by the pandemic [32]. Delayed arterial thrombosis or venous thromboembolism post-COVID-19 is an emerging health problem [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Long-COVID-19 emerges as a new aspect of the public health crisis triggered by the pandemic [32]. Delayed arterial thrombosis or venous thromboembolism post-COVID-19 is an emerging health problem [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated that during early recovery, those who went on to develop PASC generally had higher levels of cytokine biomarkers including TNF-α, IFN-γ–induced protein 10 and IL-6 ( Peluso et al., 2021 ), consistent with increased immune activation. Some speculate that persistent viral RNA shedding triggers chronic immune activation ( Desimmie et al., 2021 ; Fernández-Lázaro et al., 2021 ). Immune system dysregulation in long COVID is characterized by increased interferon gamma (IFN-γ) and interleukin (IL)-2, pathological changes in CD4 + , CD8 + lymphocyte subsets, monocyte CD14 + and CD16 + subsets, and defects in B lymphocytes and monocytes.…”
Section: Pathophysiology Of Long Covid Thrombotic Complicationsmentioning
confidence: 99%
“…Immune system dysregulation in long COVID is characterized by increased interferon gamma (IFN-γ) and interleukin (IL)-2, pathological changes in CD4 + , CD8 + lymphocyte subsets, monocyte CD14 + and CD16 + subsets, and defects in B lymphocytes and monocytes. Increased oxidative phosphorylation and reactive oxygen species-related inflammatory responses displace TNF-α and IL-6-driven inflammatory responses, driving persistent symptoms and progression of long COVID ( Fernández-Lázaro et al., 2021 ). Thus chronic persistent inflammation in long COVID may stimulate ECs, platelets and other inflammatory cells, promote the upregulation of procoagulant factors, and destroy the protective function of vascular endothelium, thereby causing abnormal coagulation ( Figure 1 ) .…”
Section: Pathophysiology Of Long Covid Thrombotic Complicationsmentioning
confidence: 99%
“…The long-term consequences of the SARS-CoV-2 infection remain largely unclear. Indeed, knowledge acquired in these 2 years of pandemia allows to differentiate acute COVID-19 from the SARS-CoV-2 infection sequelae and the Long COVID Syndrome (132). Patients with acute COVID-19 manifest signs and symptoms up to 4 weeks after the onset of the infection; Patients with COVID-19 sequelae are often elderly adult males with associated comorbidities who developed a severe acute SARS-CoV-2 infection leading to structural systemic damage (132).…”
Section: Sarcopenia In the Long Covid Syndromementioning
confidence: 99%